Monthly estimates of the quantum of fertility: Towards a fertility monitoring system in Austria - Tomá Sobotka; Maria Winkler-Dworak; Maria Rita Testa; Wolfgang Lutz; Dimiter Philipov; Henriette Engelhardt; Richard Gisser (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2005)
Short-term variations in fertility and seasonal patterns of childbearing have been of interest to demographers for a long time. Presenting our detailed study of period fertility in Austria since 1984, we discuss the problems and advantages of constructing and analysing various period fertility indicators that reflect real exposure and potentially minimise the distortions caused by changes in fertility timing. We correct monthly birth data for calendar and seasonal factors and show that seasonality of births in Austria varies by birth order. Our study reveals that the methods explicitly aimed at adjusting fertility rates for tempo distortions are not suitable for computing monthly fertility rates. However, most of the timing distortions can be eliminated when using an indicator derived from the period parity progression ratios based on birth interval distributions, termed the Period Average Parity (PAP). We illustrate the insights gained from PAP and compare it with the commonly used total fertility rates in an analysis of the recent upswing in period fertility, starting in the late 2001. This investigation will serve for establishing a monitoring of monthly fertility rates in Austria.
Keywords: 300; Austria; fertility; fertility measurement; birth seasonality; Fertilität; Sozialer Indikator; Schätzung; Österreich; Fertilität